Dealing with the Archetypes Development Process for a Regional EHR System - Santos, M.R.; Bax, M.P.; Kalra, D. (Applied Clinical Informatics, 2012)
Objective: This paper aims to present the archetype modelling process used for the Health Department of Minas Gerais State, Brazil (SES/MG), to support building its regional EHR system, and the lessons learned during this process.Methods: This study was undertaken within the Minas Gerais project. The EHR system architecture was built assuming the reference model from the ISO 13606 norm. The whole archetype development process took about ten months, coordinated by a clinical team co-ordinated by three health professionals and one systems analyst from the SES/MG. They were supported by around 30 health professionals from the internal SES/MG areas, and 5 systems analysts from the PRODEMGE. Based on a bottom-up approach, the project team used technical interviews and brainstorming sessions to conduct the modelling process.Results: The main steps of the archetype modelling process were identified and described, and 20 archetypes were created.Lessons learned:– The set of principles established during the selection of PCS elements helped the clinical team to keep the focus in their objectives;– The initial focus on the archetype structural organization aspects was important;– The data elements identified were subjected to a rigorous analysis aimed at determining the most suitable clinical domain;– Levelling the concepts to accommodate them within the hierarchical levels in the reference model was definitely no easy task, and the use of a mind mapping tool facilitated the modelling process;– Part of the difficulty experienced by the clinical team was related to a view focused on the original forms previously used;– The use of worksheets facilitated the modelling process by health professionals;– It was important to have a health professional that knew about the domain tables and health classifications from the Brazilian Federal Government as member in the clinical team.Conclusion: The archetypes (referencing terminology, domain tables and term lists) provided a favorable condition for the use of a controlled vocabulary between the central repository and the EMR systems and, probably, will increase the chances of preserving the semantics from the knowledge domain. Finally, the reference model from the ISO 13606 norm, along with the archetypes, proved sufficient to meet the specificities for the creation of an EHR system for basic healthcare in a Brazilian state.
Keywords: Health information systems; electronic health record; archetype modelling; two-level modelling; archetypes; ISO 13606; openEHR